From 0D-complex to 3D-MOF: changing the antimicrobial activity of zinc(II) via reaction with aminocinnamic acids - d’Agostino, Simone; Macchietti, Laura; Turner, Raymond J.; Grepioni, Fabrizia (Frontiers in Chemistry, 2024)
Combining zinc nitrate with 3- and/or 4- aminocinnamic acid (3-ACA and 4-ACA, respectively) leads to the formation of the 0D complex [Zn(4-AC)2(H2O)2], the 1D coordination polymer [Zn(3-AC)(4-AC)], and the 2D and 3D MOFs [Zn(3-AC)2]∙2H2O and [Zn(4-AC)2]∙H2O, respectively. These compounds result from the deprotonation of the acid molecules, with the resulting 3- and 4-aminocinnamate anions serving as bidentate terminal or bridging ligands. All solids were fully characterized via single crystal and powder X-ray diffraction and thermal techniques. Given the mild antimicrobial properties of cinnamic acid derivatives and the antibacterial nature of the metal cation, these compounds were assessed and demonstrated very good planktonic cell killing as well as inhibition of biofilm growth against Pseudomonas aeruginosa, Escherichia coli, and Staphylococcus aureus.